Kelimpahan Transendental: Pondasi Teo-Kosmologis Ekonomi Islam - Sandimula, Nur Shadiq (TSAQAFAH, 2024)
The modern Western civilization infused with the dominance of humanism and secularism has pushed religion away from being involved in scientific developments. The invested paradigm also devoted and flourished in conventional economics disciplines, and unfortunately, the concept is also attached to Islamic economics. One of the doctrines constructed is the cosmological doctrine, which declares that resources are limited and initiates the most fundamental economic problem, scarcity. This study aims to scrutinize the cosmological presupposition in economics by utilizing the Islamic worldview conceptualized by al-Attas. The method is a descriptive-philosophical examination with a thematic analysis approach. This research reveals that God plays an active role in all myriad layers of creation which necessitates His transcendental association with the cosmos. God has names and attributes that introduce his transcendent and immanent presence in the universe. Terms in the Qur'an such as rizq, ni'mah, minnah, ala', and al-fadhl semantically indicate God's transcendental abundant sustenance in the world. The theo-cosmological concept of the Islamic worldview revealed the reality of Islamic economics perceives that resources have an unlimited source of its transcendence.